Field evaluation of typhoid conjugate vaccine in a catch-up campaign among children aged 9 months to 15 years in Sindh, Pakistan. Issue 36 (26th August 2022) - Thobani, Rozina S.; Yousafzai, Mohammad Tahir; Sultana, Shazia; Kazi, Abdul Momin; Jan, Muhammad; Rafey, Abdul; Khan, Ayub; Irfan, Seema; Ujjan, Ikram Uddin; Brown, Nick; Mårtensson, Andreas; Qamar, Farah Naz
Abstract: Background: Typhoid conjugate vaccine (TCV) has recently been introduced in the expanded program for immunization (EPI) in Pakistan. Before its introduction in routine immunization, a onetime catchup campaign among children 9 months to 15 years old was conducted in November 2019. We performed field evaluation of TCV against culture confirmed Salmonella Typhi ( S. Typhi) among 9 months to 15 years old children during the catch up campaign in Karachi and Hyderabad. Methods: A rapid assessment of blood culture confirmed S. Typhi was performed. Age eligible cases of culture confirmed S. Typhi were identified from the laboratory networks of Aga Khan University Hospital Karachi and Hyderabad, Kharadar General Hospital Karachi, and Liaqat University of Medical & Health Sciences (LUMHS) Hyderabad. Information on sociodemographic, typhoid vaccination history and antimicrobial resistance was collected using a structured questionnaire. Patient medical records and lab reports were also reviewed to collect information on diagnosis and antimicrobial susceptibility information. Information about the population vaccination coverage during catch-up campaign was obtained from the provincial EPI office. Field performance of TCV in catchup campaign was measured by calculating the effectiveness using rapid screening method which is less resource-intensive technique of calculating vaccine effectiveness (VE). Results: Overall, 968 culture confirmed typhoid cases were enrolled. Among them, 82% (793/968) were from Karachi and 18% (175/968) from Hyderabad. The average age of the participants was 5.68 years, and 54% (523/968) were male. 6% (62/968) of the culture confirmed S. Typhi cases were multidrug resistant (MDR), and 61% (586/968) were extensively drug resistant (XDR). The VE using the TCV coverage data provided by EPI was 98%. Conclusion: TCV is effective against culture confirmed S. Typhi among children aged 9 months to 15 years in the catch-up campaign setting. While typhoid vaccination can significantly decrease the burden of typhoid disease, improvements in sanitation and hygiene are necessary for the prevention of spread of enteric fever. Longer term follow up will be needed to assess the duration of protection and requirement for booster doses of TCV.